Effect of diesel-palm biodiesel fuel with plastic pyrolysis oil and waste cooking biodiesel on tribological characteristics of lubricating oil - Muhamad Sharul Nizam Awang; Nurin Wahidah Mohd Zulkifli; Muhammad Mujtaba Abbas; Syahir Amzar Zulkifli; Md Abul Kalam; Mohd Nur Ashraf Mohd Yusoff; Wan Mohd Ashri Wan Daud; Muhammad Hazwan Ahmad (Alexandria Engineering Journal, 2022)
Engine oil's lubricity and tribological properties are changed when it is diluted with unburned fuels. SAE40 lubricating oil (LO) samples were contaminated with known percentage (5%) of fuels (commercial diesel (B10), diesel-palm biodiesel (PB) blend (B30a), and diesel–PB–plastic pyrolysis oil (PPO)–waste cooking biodiesel (WCB) blends (B20, B30b, and B40)). Utilizing four-ball tester, the influence of each of these fuels on wear and frictional properties of LO was measured, and wear type on worn surfaces was examined. LO diluted by B10 had a high coefficient of friction (COF) (11.52%) with severe abrasive and adhesive wear than mineral lubricant followed by B30a (3.00%). LO mixed with quaternary fuels had a lower COF, wear scar diameter (WSD) and polishing wear. When compared to SAE40–B30a, SAE40–B30b had fewer frictional properties with adhesive wear. When compared to SAE–40 mineral lubricant, SAE40–B20 had the smallest increase in COF value (1.90%), followed by SAE40–B30b (2.17%), and SAE40–B40 (2.63%). While the WSD values for all tested samples are reduced by 3.12, 5.68, 6.33, 11.11, and 17.33%, respectively, when compared to pure lubricant for SAE40–B10, SAE40–B20, SAE40–B30a, SAE40–B30b, and SAE4–B40. PPO and WCB in B10 are found to reduce lubricant degradation when compared to diesel-PB blend and commercial diesel.